2023
DOI: 10.3390/f14020232
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Heterogeneity and Conservation Status of the Natura 2000 Priority Forest Habitat Type Tilio–Acerion (9180*) Based on Field Mapping

Abstract: Priority habitat types (HTs) within the Natura 2000 network are of the highest importance for conservation in Europe. However, they often occur in smaller areas and their conservation status is not well understood. One such HT is that of the Tilio–Acerion forests of slopes, screes and ravines (9180*). The Natura 2000 study site, Boč–Haloze–Donačka gora, in the Sub-Pannonian region of eastern Slovenia is characterized by a matrix of European beech forests and includes rather small, fragmented areas covered by T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The latter constitutes an important tool for biodiversity conservation, and the NATURA2000 network of protected areas is one of them. The study by Kermavnar et al [25], however, points out the need for adopting management and conservation measures not only based on broad habitat type definitions, but also based on the specific characteristics of each habitat and on the need to expand the nature conservation actions beyond the designated protected areas. Uprety et al [26], for instance, identified ecologically important ecosystems outside of the protected areas in the Chure region of Nepal, and point out the need for active conservation measures in the region.…”
mentioning
confidence: 99%
“…The latter constitutes an important tool for biodiversity conservation, and the NATURA2000 network of protected areas is one of them. The study by Kermavnar et al [25], however, points out the need for adopting management and conservation measures not only based on broad habitat type definitions, but also based on the specific characteristics of each habitat and on the need to expand the nature conservation actions beyond the designated protected areas. Uprety et al [26], for instance, identified ecologically important ecosystems outside of the protected areas in the Chure region of Nepal, and point out the need for active conservation measures in the region.…”
mentioning
confidence: 99%